Updates on the Activity, Efficacy and Emerging Mechanisms of Resistance to Cefiderocol - Gabriele Bianco; Matteo Boattini; Monica Cricca; Lucia Diella; Milo Gatti; Luca Rossi; Michele Bartoletti; Vittorio Sambri; Caterina Signoretto; Rossella Fonnesu; Sara Comini; Paolo Gaibani (Current Issues in Molecular Biology)
In recent years, novel antimicrobials have been developed to counter the emergence of antimicrobial resistance and provide effective therapeutic options against multidrug-resistant (MDR) Gram-negative bacilli (GNB). Cefiderocol, a siderophore cephalosporin, represents a novel valuable antimicrobial drug for the treatment of infections caused by MDR-GNB. The mechanism of cefiderocol to penetrate through the outer membrane of bacterial cells, termed “Trojan horse”, makes this antimicrobial drug unique and immune to the various resistance strategies adopted by GNB. Its broad spectrum of action, potent antibacterial activity, pharmacokinetics properties, safety, and tolerability make cefiderocol a key drug for the treatment of infections due to MDR strains. Although this novel antimicrobial molecule contributed to revolutionizing the therapeutic armamentarium against MDR-GNB, the recent emergence of cefiderocol-resistant strains has redefined its role in clinical practice and required new strategies to preserve its antibacterial activity. In this review, we provide an updated discussion regarding the mechanism of action, emerging mechanisms of resistance, pharmacokinetic/pharmacodynamic (PK/PD) properties, and efficacy data of cefiderocol against the major Gram-negative bacteria and future prospects.